Oligomerization Function of the Native Exon 5 Sequence of Ameloblastin Fused with Calmodulin - Zouharova, Monika; Herman, Petr; Bednarova, Lucie; Vetyskova, Veronika; Hadravova, Romana; Postulkova, Klara; Zemanova, Lucie; Vondrasek, Jiri; Vydra Bousova, Kristyna (ACS omega, 2025)
The evolution of proteins is primarily driven by the combinatorial assembly of a limited set of pre-existing modules known as protein domains. This modular architecture not only supports the diversity of natural proteins but also provides a robust strategy for protein engineering, enabling the design of artificial proteins with enhanced or novel functions for various industrial applications. Among these functions, oligomerization plays a crucial role in enhancing protein activity, such as by increasing the binding capacity of antibodies. To investigate the potential of engineering oligomerization, we examined the transferability of the sequence domain encoded by exon 5 (Ex5), which was originally responsible for the oligomerization of ameloblastin (AMBN). We designed a two-domain protein composed of Ex5 in combination with a monomeric, globular, and highly stable protein, specifically calmodulin (CaM). CaM represents the opposite protein character to AMBN, which is highly disordered and has a dynamic character. This engineered protein, termed eCaM, successfully acquired an oligomeric function, inducing self-assembly under specific conditions. Biochemical and biophysical analyses revealed that the oligomerization of eCaM is both concentration- and time-dependent, with the process being reversible upon dilution. Furthermore, mutating a key oligomerization residue within Ex5 abolished the self-assembly of eCaM, confirming the essential role of the Ex5 motif in driving oligomerization. Our findings demonstrate that the oligomerization properties encoded by Ex5 can be effectively transferred to a new protein context, though the positioning of Ex5 within the protein structure is critical. This work highlights the potential of enhancing monomeric proteins with oligomeric functions, paving the way for industrial applications and the development of proteins with tailored properties.